Orthodontic treatment of a severe unilateral open and crossbite, by palatal appliance with monolateral screw (by Veltri): A case report - Perović Tatjana; Aleksić Ilija; Blažej Zorica (Vojnosanitetski Pregled)
Introduction. An appliance according to Veltri is a kind of palatal construction which is rarely used in our region. It appeared as a logical consequence of the evolution of appliances for rapid palatal separation. It is primarily indicated for upper molars distalization. However, its good qualities allow the use it in case of some other orthodontic problems. Case report. The aim of this report is overview of the therapy of 14-year-old boy with asymmetry of the upper dental arch and unilateral open bite and crossbite, using the appliance according to Veltri. The plan of therapy was primarily aimed at correction of upper arch asymmetry by using appliance according to Veltri. Extraction of the lower first premolars was done and then upper and lower fixed appliance for leveling the upper and lower dental arch, normalization overjet and the depth of overlap was placed. The total duration of the therapy was two years. Conclusion. Presented combined camouflage therapy achieved a satisfactory result, regardless of the poor prognosis due to hyperdivergent growth.